Formal versus informal prekindergarten care and school readiness for children in immigrant families: A synthesis review. (October 2015) - Gottfried, Michael A.; Kim, Hui Yon
Abstract: The U.S. is witnessing two major trends in its rising cohorts of young children preparing to start school: an increase in the utilization of formal (e.g., center-based) childcare options in the year before starting kindergarten and an increase in the share of these young children who come from immigrant families. Given that many children from immigrant families in the U.S. start school at a disadvantage relative to native-born children, researchers, policy makers, and practitioners have inquired into which prekindergarten alternatives might be most effective at boosting school readiness for this group of children. This review covers the effects of formal versus informal prekindergarten alternatives in the year before entering school on a commonly-explored set of child-level academic and socioemotional indictors of school readiness for children in immigrant families in the U.S. In contrast to remaining in informal care, children in immigrant families showed fairly consistent, positive academic and socioemotional effects of attending formal prekindergarten in the year before kindergarten for children in immigrant families. Compared to native-born children in formal care, children from immigrant families in formal care showed some positive, but not as consistent, evidence of closing gaps between these two groups across school readiness indicators. Finally, there are several, noteworthy common limitations in this body of literature, which can be used to shape future research agendas and policy dialogue. Highlights: This review covers formal versus informal prekindergarten alternatives for children from immigrant families. Findings show generally promising effects of formal prekindergarten for children in immigrant families. This is evidenced across both academic and socioemotional domains of readiness.